2016
DOI: 10.1097/01.prs.0000479941.42174.f1
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Expression in Human Breast Implant Capsules

Abstract: This study demonstrates the expression of toll-like receptor 4 in myofibroblasts of capsular tissue and its correlation with estrogen receptor-β positivity. Activation of toll-like receptor 4 and estrogen receptor-β, and their interplay, may be involved in myofibroblast differentiation and in the profibrotic pathogenic process underlying capsular contracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Bachour et al in 2019 compared the expression of toll-like receptors in contracted and noncontracted capsules: they found a higher expression of TLR in contracted capsules than uncontracted, and the differences were significant for TLR-2, TLR-6 and TLR-8 [ 85 ]. The macrophage activation leads to cytokines and chemokines secretion such as IL-8 and TNF-alpha, producing an increased inflammatory response usually founded in contracted capsules [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bachour et al in 2019 compared the expression of toll-like receptors in contracted and noncontracted capsules: they found a higher expression of TLR in contracted capsules than uncontracted, and the differences were significant for TLR-2, TLR-6 and TLR-8 [ 85 ]. The macrophage activation leads to cytokines and chemokines secretion such as IL-8 and TNF-alpha, producing an increased inflammatory response usually founded in contracted capsules [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study investigated the role of TLR expression in breast capsules. Segreto et al [42], investigated the expression of TLR4 and its relationship with estrogen receptor expression. They found TLR4 expression in fibroblasts and myofibroblasts with a positive correlation with estrogen receptor-β expression in capsular contracture.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 is, however, mostly known to be one of the major receptors for the recognition of lipopolysaccharide (LPS), a ligand on Gram-negative bacteria [10, 29]. Upregulation in contracted capsules as observed by Segreto et al [42] could suggest that TLR4 is activated by the presence of bacteria. It would have been valuable if they would also have investigated bacterial presence on their capsules to strengthen this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Capsular contracture is a fibrotic process frequently observed following a breast implant placement; although its mechanisms are poorly understood, the role of fibroblasts is an active topic of research. 50 Studies have found that estrogen receptor expression by capsular myofibroblasts in patients is associated with an increased αSMA expression and capsular thickness, 51 , 52 while clinically, antiestrogenic therapy is associated with a less-severe contracture, 52 suggesting a potential therapeutic strategy for targeting capsular myofibroblasts.…”
Section: Parenchymal Fibroblasts and Organ Fibrosesmentioning
confidence: 99%